2019
DOI: 10.1001/jamanetworkopen.2019.5578
|View full text |Cite
|
Sign up to set email alerts
|

Association of Repetitive Transcranial Magnetic Stimulation Treatment With Subgenual Cingulate Hyperactivity in Patients With Major Depressive Disorder

Abstract: Key Points Question Is repetitive transcranial magnetic stimulation associated with changes in subgenual cingulate cortex (SGC) activity in patients with major depressive disorder (MDD)? Findings This diagnostic study, which compared 30 patients with MDD and 30 healthy controls, found that using transcranial magnetic stimulation combined with electroencephalography, SGC activity in patients with MDD was significantly higher compared with healthy controls. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 55 publications
1
39
0
Order By: Relevance
“…Several studies have also reported functional connectivity changes in response to repetitive TMS (rTMS) in depressed patients (Ge et al, 2017;Kito et al, 2017;Richieri et al, 2017;Du et al, 2018;Iwabuchi et al, 2019). Positive responses to rTMS have been associated with reduced connectivity of the SCC to the DMN (Philip et al, 2018), along with reduced activity of the SCC and connectivity with the DLPFC (Hadas et al, 2019), supporting the hypothesis of altered connectivity in these areas underlying depressive symptoms (Hamilton et al, 2015). Moreover, sleep-deprived healthy participants and depressed patients demonstrate alterations in functional connectivity patterns (Bosch et al, 2013;Chen et al, 2018;Kong et al, 2018).…”
Section: Examining Rapid Antidepressant Effects Through Encodingmentioning
confidence: 91%
“…Several studies have also reported functional connectivity changes in response to repetitive TMS (rTMS) in depressed patients (Ge et al, 2017;Kito et al, 2017;Richieri et al, 2017;Du et al, 2018;Iwabuchi et al, 2019). Positive responses to rTMS have been associated with reduced connectivity of the SCC to the DMN (Philip et al, 2018), along with reduced activity of the SCC and connectivity with the DLPFC (Hadas et al, 2019), supporting the hypothesis of altered connectivity in these areas underlying depressive symptoms (Hamilton et al, 2015). Moreover, sleep-deprived healthy participants and depressed patients demonstrate alterations in functional connectivity patterns (Bosch et al, 2013;Chen et al, 2018;Kong et al, 2018).…”
Section: Examining Rapid Antidepressant Effects Through Encodingmentioning
confidence: 91%
“…Two recent studies illustrate the potential of this approach. In one study, the activity of the subgenual cingulate cortex and its effective connectivity with the DLPFC was calculated using TMS‐EEG before and after a course or rTMS to treat adult major depression . Subgenual cingulate activity is increased in major depression and is anticorrelated with DLPFC activity.…”
Section: Tdcs In Admentioning
confidence: 99%
“…In one study, the activity of the subgenual cingulate cortex and its effective connectivity with the DLPFC was calculated using TMS-EEG before and after a course or rTMS to treat adult major depression. 28 Subgenual cingulate activity is increased in major depression and is anticorrelated with DLPFC activity. The study found that subgenual cingulate excitability and connectivity were increased in major depression and that changes in these measures were specific to receiving active rTMS vs. sham rTMS.…”
Section: Transcranial Magnetic and Electrical Stimulation In Alzheimementioning
confidence: 99%
“…PET studies also demonstrated increased blood flow of the SGC co-occurring with instances of sadness and depression, and recovery from depression showed the SGC hyperactivity being normalized 7 . SGC hyperactivity normalization was also demonstrated after different lines of treatments for MDD, such as antidepressant drugs [15][16][17][18] , repetitive transcranial magnetic stimulation (rTMS) 13,19,20 and ECT 21 . These findings led to efforts to treat MDD by implanting deep-brain stimulation electrodes at the SGC white matter 22 .…”
Section: Introductionmentioning
confidence: 96%
“…The subgenual cingulate cortex (SGC) is extensively implicated in the pathophysiology of MDD. There are evidence from studies utilizing positron emission tomography (PET) [5][6][7] , functional magnetic resonance imaging (fMRI) [8][9][10][11][12] , electroencephalography (EEG) 13 , and postmortem assessments 14 which closely tie the SGC with the pathophysiology of MDD. The SGC grey matter volume, PET cerebral blood flow and glucose metabolism have been found to be abnormal in MDD patients 6 .…”
Section: Introductionmentioning
confidence: 99%